From Teachers’ Views to Explore the Implementation of Energy Education in Taiwan’s Elementary Schools - Mei-Ching Chen; Chin-Cheng Chou; Chao-Ti Hsiung (JIPF (Jurnal Ilmu Pendidikan Fisika), 2020)
This study intended to explore the implementation of promoting “energy education” in Taiwan’s elementary schools. The research adopted a questionnaire (Likert five-point scale) from teachers’ view in three dimensions to construct examination. The 45 participants come from 10 different primary schools distributed across Taiwan, which participate in energy education program in the second period (2015-2017). The data was analyzed by ANOVA, mean and standard deviations of the viewpoints of the participants in the energy education learning achievement of the primary schools. The first findings in this research is, the program of energy education was most effective in “energy attitude” (M=4.282, SD=0.814), followed by “energy awareness” (M=4.049, SD=0.720) and “energy behavior” (M=3.983, SD=0.875). It shows that students have positive energy attitude, but they were relatively weak at energy saving behavior. Secondly, there is statistically significant difference in overall students learning performance with urban areas are higher than rural areas. Finally, it is suggested that in addition to strengthen energy attitudes and energy awareness, we should encourage students to take action in save energy in their daily life. Furthermore, we should invest more resources to rural areas to balance the students’ performances between urban and rural areas.